Pelatihan Manajemen Ritel Bagi UMKM Toko Kelontong sebagai Bentuk Kerjasama Perguruan Tinggi dan Mitra Industri - Agustina, Tri Siwi (Eastasouth Institute, 2024)
The presence of minimarkets that are getting closer to residents in housing and the presence of technology has changed the behavior of retail store consumers from shopping at grocery stores that tend to be managed conventionally to modern stores. Based on this phenomenon, this collaboration activity between FEB UNAIR and BULOG for East Java Region was carried out. The Retail Management Training was held in November with a target audience of 35 grocery store owners in Tegalsari District. The training was carried out by lecture method, and question and answer. The positive response from participants is good news for the implementation of SUIC and is expected to be sustainable. It is realized that this activity is still far from perfect in equipping grocery store’s owners, therefore, in order to be sustainable, it is hoped that there will be further activities so that grocery stores in Tegalsari District can attract buyers and be competitive.